LEGAL MEASURES IN ADDRESSING NARCOTIC CRIMINAL ACTIONS AMONG STUDENTS: UPAYA HUKUM DALAM MENANGANI TINDAK PIDANA NARKOTIKA DI KALANGAN PELAJAR - Harfiyana (UPMI Proceeding Series, 2023)
Narcotics can be present in people's lives, it is possible for someone named a student to be detected in drug use. The purpose of this writing is to find out the rules for students who use drugs. The type of research in this paper is empirical with a statutory and conceptual approach. The research specifications are analytical descriptive. The data used is empirical which consists of primary legal materials and secondary legal materials. The data analysis method was carried out qualitatively. Rules for students who use drugs are regulated in Law no. 35 of 2009 concerning narcotics which is the basis for preventing and eradicating the abuse and illicit traffic of narcotics which is very detrimental and endangers the life of society, nation and state. Meanwhile, based on Law no. 35 of 2009 Article 1 Number 13 what is meant by drug addicts are people who use or abuse narcotics and are in a state of dependence on narcotics both physically and psychologically. For this reason, it is recommended that the public, especially among students, never approach narcotics, let alone consume them, because the sanctions are quite severe.